USING GAMES IN THE CLASSROOM - Mirzayeva Mahbuba Mamajonovna; Mukhtorova Gulchiroy (Ta'lim innovatsiyasi va integratsiyasi, 2023)
Abstract - This article highlights the benefits of using games and the engagement between lessons and educational games in the class.